2015
DOI: 10.2196/jmir.3749
|View full text |Cite
|
Sign up to set email alerts
|

Health Information–Seeking Behavior of Seniors Who Use the Internet: A Survey

Abstract: BackgroundThe Internet is viewed as an important source for health information and a medium for patient empowerment. However, little is known about how seniors use the Internet in relation to other sources for health information.ObjectiveThe aim was to determine which information resources seniors who use the Internet use and trust for health information, which sources are preferred, and which sources are used by seniors for different information needs.MethodsQuestions from published surveys were selected base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(104 citation statements)
references
References 18 publications
(18 reference statements)
7
94
0
3
Order By: Relevance
“…Campbell (2009) studied the effect of an educational intervention on seniors in order to empower them to seek information online for directing their own care. In agreement with the findings related to the context above, much of the research that fits within this area also focuses either on online seeking or considers Internet use as a primary means by which to better inform the individual in preparation of decision making (Campbell, 2009;Deng & Liu, 2017;Ellis et al, 2012;Medlock et al, 2015;Roettl et al, 2016).…”
Section: Hisb In the Context Of Participation And Involvement In Medisupporting
confidence: 56%
See 1 more Smart Citation
“…Campbell (2009) studied the effect of an educational intervention on seniors in order to empower them to seek information online for directing their own care. In agreement with the findings related to the context above, much of the research that fits within this area also focuses either on online seeking or considers Internet use as a primary means by which to better inform the individual in preparation of decision making (Campbell, 2009;Deng & Liu, 2017;Ellis et al, 2012;Medlock et al, 2015;Roettl et al, 2016).…”
Section: Hisb In the Context Of Participation And Involvement In Medisupporting
confidence: 56%
“…Social networks (Wonsun et al, 2015) and families (Noh et al, 2016) were found to positively impact HISB and willingness to undergo treatment (Roettl et al, 2016). Other external contextual factors that affect HISB may be the result of participation in information seeking training (Campbell, 2009), immigration status (N€ olke et al, 2015), language and cultural norms (Todd & Hoffman-Goetz, 2011) or simply an upcoming doctor's appointment (Medlock et al, 2015). The actual information being found can, itself, influence further information seeking.…”
Section: Antecedentsmentioning
confidence: 99%
“…Thus, having internet access as well as differential perceptions in usefulness might be considered potential motives for adopting new technologies. This consideration is especially important in the context of health, as several studies purport the benefits of health information seeking, especially for older adults (e.g., Medlock et al, 2013, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, approximately 55.1% of the world's total population are Internet users (Internet World Stats, 2018). Increasing participatory Internet use as an important health information source and patient empowerment medium for health decision-making and behaviours has been reported among older adults (Medlock et al, 2015). As such, there is increased advocacy to integrate the eHealth platform to deliver the care components of CR in a way that can best address the more individualized healthcare needs of cardiac patients to generate more health benefits (Paige, Krieger, Stellefson, & Alber, 2017).…”
Section: Introductionmentioning
confidence: 99%